2008
DOI: 10.1002/hec.1389
|View full text |Cite
|
Sign up to set email alerts
|

Stress perception and commuting

Abstract: SUMMARYThis paper analyzes the determinants of the perceived stress level of workers with a special focus on the effects of commuting, while controlling for personal and work-related characteristics. Using ordered logistic regression we find that several dimensions of the commuting situation, such as impedance, control and predictability of commuting, significantly influence the perceived stress level. Therefore, stress and stress-related health problems should be taken into consideration when analyzing the ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(134 citation statements)
references
References 26 publications
(37 reference statements)
8
113
0
5
Order By: Relevance
“…15 As other variables may impact upon enjoyment of the commute, we also included in the models: minutes of physical activity, reporting feeling rushed or pressured and perception that their neighbourhood is more pleasant compared with 12 months ago. 4,16 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 As other variables may impact upon enjoyment of the commute, we also included in the models: minutes of physical activity, reporting feeling rushed or pressured and perception that their neighbourhood is more pleasant compared with 12 months ago. 4,16 …”
Section: Methodsmentioning
confidence: 99%
“…3 Several dimensions of commuting influence perceived stress, such as impedance (caused by traffic congestion), and control over and predictability of commuting. 4 Inactivity associated with motor vehicle travel has been linked to the risk of being overweight or obese, 5 and motor vehicle commuters report higher levels of stress compared with active travel modes. 6 However, there are benefits and disadvantages associated with each travel mode, and in many cities people still chose to drive to work and presumably derive some satisfaction or enjoyment from it (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, individuals who commute may have better, more motivating jobs and be able to achieve a better work-life balance. Furthermore, willingness to travel to work may be associated 1 Several predominantly U.S. studies have found that work commutes induce stress due to their unpredictability and the perceived loss of control (Gottholmseder et al, 2009). Furthermore, commuting has been shown to be associated with increased heart rate and blood pressure (Novaco et al, 1979;Schaeffer et al, 1988).…”
mentioning
confidence: 99%
“…Most studies used varying combinations of the following criteria: commute (measured in time or distance, often broken into groups by severity of length/distance), length of time regularly commuting (how long have you been commuting "x" miles? ), education level, and income level (Gottholmseder et al, 2009;Nivens & Nordstrom, 2012;Sposato et al, 2012;Wener & Evans, 2011). Collecting such demographic information is critical for assessing the generalizability of one study's findings to the broader population of commuters.…”
Section: Common Methodological Approachesmentioning
confidence: 99%